THE CONCEPT OF “FREEDOM” IN SPAIN (1770-1870) - Chacón Delgado, Pedro José (Revista de Historia Social y de las Mentalidades, 2024)
As a consequence of the revolutionary events  in Cadiz, the concept of ‘liberty’ in Spain  became one of the clearest distinguishing  marks of political modernity. It would be  the nucleus around which to a great extent  political debate and the country’s public life as  a whole would henceforth revolve. The conflict  regarding its meaning would form an essential  part of political combat and ideological  demands amongst not only those forces  fighting for a more or less drastic change in the  Old Regime, but also those who continued to  defend it from a constitutionalist standpoint.  This work details the changes in meaning of  the concept of liberty and its different uses  in conjunction with the various adjectives  which define it (natural, civil, political, etc)  throughout political history and the diverse  ideological options which arose during each of  the historical subperiods which constituted the  cycle 1770-1870.
Keywords: natural law; constitution; liberty; conceptual history